Photocatalytic abatement of formaldehyde under visible light irradiation via bamboo carbon/TiO2 modified by plasma at low temperature. (1st October 2022) - Tan, Yujie; Zhao, Weixuan; Sun, Luying; Zhang, Renxi; Hou, Jianyuan; Fu, Shaoxiang; Xu, Weien; Zhang, Ruina
Abstract: A new catalyst modified by plasma was investigated to substantively improve the photoactivity of TiO2 for formaldehyde abatement. Pure anatase TiO2 mechanically mixed with biochar was fabricated by H2 plasma (denoted as C/TiO2 ) under low temperatures (<397 K). C/TiO2 exhibited a high and long-lasting activity and remove approximately 73.7% of formaldehyde within 3 h under a simulated visible light irradiation; this is much higher the corresponding values using untreated TiO2 and untreated mixtures (denoted as un-C/TiO2 ). It is concluded that, following H2 plasma treatment, the addition of 5% biochar to the catalyst had the best removal efficiency due to increased meso/microporous structures, a decreasing bandgap and diminishing recombination rate of electron–hole pairs. During the process, the surface active-oxygen groups including –OH increased from 19% to 24%. These results also reveal that the catalyst could be etched by high-energy electrons in order to gain better surface properties for formaldehyde degradation. This new plasma-assisted catalyst has enhanced visible light photoactivity and a boosted capture ability and could thus have promising applications to volatile organic compounds. Highlights: A plasma-assisted method to fabricate TiO2 combined with bamboo carbon was firstly studied. The catalyst has an enhanced visible light absorption and a boosted capture ability. The catalyst showed a better performance for formaldehyde removal.